Analisis Perbedaan Harga Saham, Volume Perdagangan Saham, Return Saham Dan Volatilitas Harga Saham Sebelum Dan Sesudah Stock Split Periode 2020-2023 - Imas Nur Fadilah; Denia Maulani; Muhammad Zakie Hanifan (CV. ITTC INDONESIA, 2025)
This research aims to determine differences in stock prices, trading volume, stock returns and stock price volatility before and after the stock split in companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The population in this research are all companies listed on the Indonesia Stock Exchange (BEI) that implemented a stock split policy during the 2020-2023 period. Sampling in this study used a purposive sampling method, based on predetermined criteria, a sample size of 32 companies was obtained. The method used is different tets analysis with observation periods -7 (7 days before the stock split), +7 (7 days after the stock split) and -3 (3 days before the stock split), +3 (3 days after the stock split). Hypothesis testing in this research was carried out using the Paired Sample T- Test which was used for normally distributed data and the Wilcoxon Signed Rank Test used for data which was not normally distributed. Based on the research results, it was found that there were differences in stock prices before and after the stock split, there were differences in stock trading volume before and after the stock split and there were no differences in stock returns before and after the stock split and there is no difference in stock price volatility before and after stock split.